E-RETAILING IN INDIA: GROWTH, TRENDS, AND EMERGING CHALLENGES - S.Jayalakshmi, (mLAC Journal for Arts, Commerce and Sciences (m-JACS) ISSN: 2584-1920, 2024)
E-retailing is the activity of selling consumer items online. In essence, it is a modernization of online sales of products and services as well as a revolution in e-business and e-commerce. Because of technology development, e-retailing has become a new idea in retailing. The present era is rife with fresh issues; fashions of today become dated tomorrow, and a fresh problem emerges. As a result, businesspeople are constantly alert to dangers and changes in the market. E-retailing is the process of selling retail items online, which is advantageous to customers who are time-constrained but desire a wide selection of goods at affordable prices.